Spillover Effects of Energy Transition Metals in Chile - Pablo Agnese; Francisco Rios (Institute of Labor Economics (IZA), 2023)
This paper examines the impact of spillover effects of energy transition metals on the Chilean economy. With the increasing demand for metals like copper and lithium due to the growth in renewable energies and electromobility, metal abundant countries like Chile must ready themselves to remain active players in the international arena. The study aims at identifying the causal relationships among these energy transition metals and other major assets like gold and bitcoin, and how they have given shape to Chile's economy, especially during the uncertain times of the covid pandemic. Our Structural Vector Autoregressive models suggest that Chile has been more prone to US-led shocks than Chinese shocks, even though its economy depends heavily on China. In addition, bitcoin shocks seem to have also contributed to Chile's transition to a metals-based economy, likely as a result of bitcoin's extensive use of energy and the uncertainty and volatility that characterize post-covid times.
Keywords: F62; G15; L61; 330; copper; lithium; COVID-19; SVAR